Severe Stenosis of an Anomalous Circumflex Artery Mimicking a Chronic Total Occlusion - George Mawardi; Anbukarasi Maran (Case Reports in Cardiology)
The prevalence of anomalous circumflex coronary arteries is rare. Identifying the presence of an anomalous coronary is quite easy when there is no severe stenosis. However, in the presence of severe stenosis, there is limited anterograde flow, which makes it challenging to visualize the course of the stenotic artery, and it can be assumed to be a chronic total occlusion (CTO). This case demonstrates how the anomalous circumflex artery with severe stenosis masqueraded as a CTO and the patient was treated medically for several years, despite continued symptoms. The retrograde filling of an anomalous circumflex has a specific angiographic pattern which should be recognized. This case is an excellent illustration of the said angiographic pattern.